FORMULATION, PHYSICO-CHEMICAL AND SENSORY ASSESSMENT OF INSTANT DHOKLA MIXES PREPARED WITH RED AND WHITE KIDNEY BEAN FLOURS - CH. SOUMYA*, J. LAKSHMI, K. LAKSHMI and M.S. BAIG (The Journal of Research ANGRAU, 2023)
Value added instant dhokla mixes were prepared by partially replacing the basic dhokla recipe consisting of besan flour (BF) with red kidney bean flour (RKBF) and white kidney bean flour (WKBF) in the year 2021-2022. Four variations of dhoklas were prepared with RKBF and WKBF in the ratio 2:1, 1:2, 1:1 and 0:1 of BF and KBF, respectively and were organoleptically evaluated with 9-point hedonic ranking scale. The mean scores obtained from a panel of 25 judges indicated that the incorporation of KBF in the ratio 2:1 was rendered most acceptable in terms of color (8.36, 8.1), appearance (8.4, 8.4), flavor (8.2, 8.2), taste (8.28, 8.3), texture (8.2, 8.1) and overall acceptability (8.48, 8.1) for dhoklas prepared from RKBF and WKBF, respectively. The nutritional composition of the most accepted formulations of instant dhokla mixes prepared from RKBF and WKBF were, moisture (5.24. 5.16%), protein (15.86, 17.91 g), fibre (1.96, 1.60 g), fat (3.42, 3.16 g), calcium (56.3, 54.39 mg) and iron (5.05, 5.1 mg), respectively